UJI AKTIVITAS ANTIOKSIDAN DARI EKSTRAK DAUN Tilia kiusiana (Antioxidant Activity Assay of Tilia kiusiana Leaf Extract) - Amalia Indah Prihantini (Balai Penelitian Dan Pengembangan Teknologi Hasil Hutan Bukan Kayu, 2017)
There are many of the world’s biodiversity has not been evaluated for any biological activity. To explore the pharmacological potency of nature, the present study investigated antioxidant activity assay of Tilia kiusiana, a Japanese lime tree. Methanolic leaf extract of T. kiusiana was used to analyze the antioxidant assays. The result showed that the extract had moderate activity on antioxidant assays such as DPPH radical scavenging activity (IC50 232.76±1.13µg/mL), reducing power (53.33±1.57 mg QE/g dry extract); hydrogen peroxide (304.49±4.57 µg/mL), and β-karoten (45.80±1.68 µg/mL). The Total Phenolic Content (TPC) revealed that the extract had low values for gallic acid, quercetin, and rutin equivalents (49.29±3.82 mg QE/g dry extract; 36.57±3.01 mg QE/g dry extract; 90.44±7.23 mg QE/g dry extract, respectively). In conclusion, the present study supported the investigation on discovery and resupply of pharmacological active plant-derived natural products.